Grundtvig og rationalisterne - Glebe-Møller, Jens (Grundtvig-Studier, 2011)
Grundtvig og rationalisterne [Grundtvig and rationalist theology] By Jens Glebe Møller As is well known, Grundtvig disliked the Enlightenment and was a staunch opponent of the rationalist theology in his own days as well as in the 17th century. In this essay rationalist theology and its philosophical background is briefly presented as well as an article by Grundtvig from Theologisk Maanedsskrift 1825, in which he vehemently criticises the Enlightenment and, according to him, the widespread influence of rationalist theology in Denmark. A sermon from 1789, as well as the notes taken by Bishop Mynster in his Visitatsdagbøger (Journals of pastoral visitations), corroborate Grundtvig’s statement. However, Grundtvig himself was in more than one aspect an heir to the rationalists he so much despised. For one thing, in all his writings he revered the “truth-loving” reason and adhered to the principle of contradiction. Furthermore, like all the rationalist theologians he denied the dogma of the hereditary sin and devaluated the importance of the creeds of the primitive church as well as of The Augsburg Confession of the Lutheran Churches. While definitely a theologian in his own right, it would be wrong to completely sever Grundtvig from his rationalist heritage.